A CONCEPTUAL REVIEW OF BHASMA PARIKSHA WITH A MODERN VIEW - Bhange P.V; Bhatambre Y.S. (International Journal of Applied Ayurved Research, 2017)
Bhasma is one of the unique preparations described in Rasashastra. Bhasma is prepared by incinerating the metals and minerals. In Rasagrantha, various pariksha (Tests) have been described to ascertain the complete preparation of bhasma. Specific pariksha like Rekhapurna, Varitar, Unam, Niswadu, Apunarbhava, Niruttha, etc. have been described for this purpose. Free metal remained in the bhasma after the puta procedure (Heating) could be fatal, so these pariksha are necessary to be carried out. Ancient Rasacharya were well aware regarding the side effects of the improper bhasma, so they have described these tests to ascertain the preparation of proper bhasma.Also while studying these pariksha with the modern view; it seems very important to test bhsama by applying these pariksha. Each pariksha has been described here with its modern view. It could be helpful to study and standardize the bhasma pariksha with classical and modern view.